Fatty acids and free amino acid composition of synbiotic goat cheese with free and encapsulated probiotics - Nazan Kavas; Gökhan Kavas; Özer Kınık; Mustafa Ateş; Gülçin Şatır; Muammer Kaplan (Mljekarstvo)
The aim of this study was to determine the changes in free fatty acids and amino acids during storage of synbiotic microcapsule-added goat cheeses and determine the effect of microencapsulation on these changes during storage. Another objective was also to determine the effects of probiotics and synbiotics (probiotic + prebiotics) added in free form during the production of white goat cheese on amino acid and fatty acid values. In the study, three types of microcapsules including probiotic bacteria (Lacticaseibacillus casei and Bifidobacterium longum), probiotic + fructooligosaccharide (FOS), and probiotic + inulin containing microcapsules were prepared and cheeses were produced using these microcapsules. Cheese samples were stored at +4 °C for 180 days and the amino acids and free fatty acid content of the cheeses were determined during the storage period. The saturated fatty acid with the highest ratio in goat cheeses was palmitic acid (C16) whereas the unsaturated fatty acid with the highest ratio was determined as oleic acid (C18:1). At the end of ripening, the amino acid with the highest amount was glutamic acid in cheese samples, followed by leucine, proline, aspartic acid, and lysine, respectively. It has been determined that inoculation of probiotic cultures, either in free or microencapsulated form, into cheese milk positively influences the total amino acid and fatty acid levels. The addition of inulin along with probiotics on the 180th day of storage was effective in amino acid formation compared to cheeses with free FOS added. It could also be concluded that the addition of free or microencapsulated FOS was effective in the formation of free fatty acids. In addition, regardless of the used form (free or microcapsules), inulin was more effective in amino acid formation.